Dissociation of the role of the prelimbic cortex in interval timing and resource allocation: beneficial effect of norepinephrine and dopamine reuptake inhibitor nomifensine on anxiety-inducing distraction - Matthews, Alexander R.; He, Olivia H.; Buhusi, Mona; Buhusi, Catalin V. (Frontiers in Integrative Neuroscience, 2012)
Emotional distracters impair cognitive function. Emotional processing is dysregulated in affective disorders such as depression, phobias, schizophrenia, and PTSD. Among the processes impaired by emotional distracters, and whose dysregulation is documented in affective disorders, is the ability to time in the seconds-to-minutes range, i.e. interval timing. Presentation of task-irrelevant distracters during a timing task results in a delay in responding suggesting a failure to maintain subjective time in working memory, possibly due to attentional and working memory resources being diverted away from timing, as proposed by the Relative Time-Sharing model. We investigated the role of the prelimbic cortex in the detrimental effect of anxiety-inducing task-irrelevant distracters on the cognitive ability to keep track of time, using local infusions of norepinephrine and dopamine reuptake inhibitor nomifensine in a modified peak-interval procedure with neutral and anxiety-inducing distracters. Given that some antidepressants have beneficial effects on attention and working memory, e.g., decreasing emotional response to negative events, we hypothesized that nomifensine would improve maintenance of information in working memory in trials with distracters, resulting in a decrease of the disruptive effect of emotional events on the timekeeping abilities. Our results revealed a dissociation of the effects of nomifensine infusion in prelimbic cortex between interval timing and resource allocation, and between neutral and anxiety-inducing distraction. Nomifensine was effective only during trials with distracters, but not during trials without distracters. Nomifensine reduced the detrimental effect of the distracters only when the distracters were anxiety-inducing, but not when they were neutral. Results are discussed in relation to the brain circuits involved in Relative Time-Sharing of resources, and the pharmacological management of affective disorders.